AKT/GSK-3 Pathway Targeting; Botanicals and Bioactive Compounds with Anticancer Activities - Jalali, Atefeh; Zarshenas, Mohammad M. (Current Pharmaceutical Design, 2021)
Background: In the late 20th century, the leading role of signaling pathways in various cancers is revealed via some genome's systematic investigations. The Akt/GSK-3 signaling pathway is one of the critical signaling pathways dysregulated in numerous human cancers. The Akt cascade acts in the cancer process by regulating apoptosis, cell cycle, metabolism, and cells' longevity. The GSK-3 is downstream of Akt, which has an opposite role in cancer progression. Objective: Attending to the importance of the Akt/GSK-3 pathway in cancer progression and the positive result of natural products in cancer treatment, this research is designed to review effective herbal medicines in one of the involvement critical signal pathways of cancer for developing novel anticancer drugs. Method: Keywords
Keywords: cancer